Sequence and analysis of BECV F15 matrix protein - Savoysky, E. (Res Virol, 1990)
Clones from the bovine enteric coronavirus (F15) cDNA library were cloned in pBR322 and sequenced by the method of Sanger and Coulson. This led to the identification of a sequence of 1,300 bases which contained a single open reading frame of 690 bases yielding a protein having properties of the matrix protein (M). It was comprised of 230 amino acids with a molecular weight of 26,376 Da. It was hydrophobic and had a net charge of +8 at neutral pH. Analysis of its secondary structure could not establish a simple transmembrane arrangement of the amino acids. Comparison of its nucleotide sequence with that of BECV Mebus strain showed only a two-base change resulting in a 100% homology between the two amino acid sequences. Furthermore, a very conserved structure of M appeared on comparison with the Dayoff optimal alignment of MHV-A59, MHV-JHM, TGEV, IBV Beaudette and IBV 6/82M amino acid sequences. As the two strains of BECV, F15 and Mebus present some antigenic differences, this led us to reconsider the role of M in viral antigen specificity. A hypothesis is that, as it seems to possess the necessary information on its transmembrane region, it is an ideal candidate for the viral budding process.